Contesting Hierarchies and Multiple Identities: Conflict and Development in Bodoland - Anju Chaudhari (Dera Natung Government College Research Journal)
The post-colonial Indian state, the colonial legacy of communalism and various exclusivist identity-related movements have been significant forces in the Assamese political arena. Consequently, the displacement of the Assamese population has been greatly influenced by their exertion at specific junctures. Ethnicity, which becomes a fundamental element in the identification of dichotomies and emergence of conflicts rests upon symbolic resources and affective ties. Bodoland Territorial Council (BTC) is one of the most ethnically disputed corridors of lower Assam. The region has attracted the attention of national and international media for one of the most large-scale ethnic displacements in post-colonial modern India. The question of being indigenous and the fear of becoming a minority in an area which was once dominated by Bodos, has led to the eruption of a movement which `later on became a violent conflict. In this paper, I shall try to address underlying issues leading to ethnic acrimony within the diverse Assamese society with reference to the historical and demographic backdrop of Bodoland. The paper seeks to de-construct the proposed models of development as a solution for conflicts. Thereby, the argument would be made for decentralization of decision-making authority and power-sharing strategy directed by local leadership. Furthermore, the paper acknowledges that the side-lining of non-dominant ethnic groups has led to the continuation of hostilities within the region. The last section highlights the significant role of civil society and the implementation of affirmative action which becomes critical for securing political rights for inadequately represented communities which may grant them political authority and social legitimacy.